PENGARUH PERSEPSI KEMUDAHAN BERDONASI, DAN EFEKTIFITAS PENYALURAN MENGGUNAKAN FINTECH CROWDFUNDING TERHADAP MINAT MEMBAYAR ZAKAT, INFAQ, SHADAQOH - Isnaini Lailatul Rohmah; Ibdalsyah Ibdalsyah; Ahmad Mulyadi Kosim (Kasaba, 2020)
The purpose of this study was to determine the effect of perceived ease of donating and the effectiveness of the distribution of ZIS interest using fintech crowdfunding. Sample this research is 86 respondents of students at the Islamic Studies Faculty of UIKA Bogor. The data collection method uses a questionnaire and the technical analysis used is multiple linear regressions. The results showed the variable Ease of Donation Ease of Interest in ZIS Using Fintech Crowdfunding had a negative effect on the significant value of t count of 0.253, indicating that if the ease of donating was easier to use then the interest of students in doing ZIS Using Fintech Crowdfunding would increase. Variable Effectiveness of Distribution of ZIS Interest Using Fintech Crowdfunding has a positive effect on the significant value of a count of 0,000. There shows the effectiveness of distribution gives confidence to students in conducting ZIS using Fintech Crowdfunding. And according to ANOVA analysis results show that the calculated F value of 30.115 with a significance value of 0,000. This shows that the Perception of Ease to Donate, Effectiveness Distribution jointly, or simultaneously influences the Interest of ZIS Using Fintech Crowdfunding.